Innovation in regeneration of graphene and nmc electrodes from lithium-ion battery waste through an environmentally friendly method - Jesaya Hansel (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2025)
Background: The problem of lithium-ion battery (LIB) waste that has not been optimally addressed poses serious risks to the environment and strengthens dependence on primary metal mining. The limited availability of efficient and environmentally friendly recycling methods encourages the need for innovative approaches in the recovery of active materials from used electrodes. This study aims to evaluate the potential of a combination of two alkali-acid regeneration methods for graphene- based anodes and low-temperature molten salt for Nickel Manganese Cobalt (NMC) cathodes as a sustainable strategy in LIB waste treatment. Methods: The study was conducted through a critical literature review of various national and international scientific publications, focusing on the purification effectiveness, morphological characteristics, crystal structure, and electrochemical performance of the regenerated materials. Findings: The analysis results show that the alkali-acid method is effective in selectively removing impurities and is able to increase the specific capacity of the anode to 359 mAh/g, approaching the theoretical capacity of commercial graphene . Meanwhile, the NMC cathode regenerated through the molten salt method and combined with graphene through a simple solid-state mixing showed a capacity of 158.1 mAh/g at a current of 0.5C with good cycle stability. The integration of these two methods synergistically improves electron conductivity, cycle efficiency, and electrode structural stability. In addition to its technical advantages, this approach also utilizes relatively safe and readily available chemicals, making it relevant for both laboratory and industrial applications. The proposed process is competitive with commercial materials and has the potential to be implemented in the economical and industrial-scale remanufacturing of 18650 batteries. Conclusion: These findings significantly contribute to strengthening the battery recycling ecosystem in Indonesia and support the achievement of sustainable energy targets. Furthermore, reducing the volume of hazardous and toxic waste (B3) and optimizing the reuse of high-value materials support the implementation of circular economy principles that align with national policies in the energy and environmental sectors. Novely/Originality of this article: The novelty of this research lies in the integration of two selective and environmentally friendly regeneration methods in one processing system, which has not been widely developed in previous literature, thus offering a new applicable framework for LIB waste processing towards sustainable industrialization.